Analysis of the Influence of Sea Surface Temperature Anomalies on Changes in Small Pelagic Fisheries Productivity in the Northern Waters of East Jawa - Andi Darmawan; Rina Awaliyah Putri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Sea surface temperature anomalies play an important role in regulating marine ecosystem productivity and small pelagic fisheries in tropical waters. This study analyzes the relationship between sea surface temperature (SST) anomalies, chlorophyll-a variability, and small pelagic fisheries productivity in the northern waters of East Java based on an integrative literature review and secondary oceanographic data synthesis. The study compiles findings from satellite-based observations and fisheries catch records across Indonesian waters. Results indicate that SST anomalies strongly influence chlorophyll-a distribution and subsequently affect fish aggregation and catch variability. Upwelling and ENSO–IOD interactions significantly regulate nutrient availability, leading to seasonal shifts in fishing grounds. Several studies confirm that optimal SST ranges between 27°C and 30°C support high pelagic fish productivity, while deviations reduce catch efficiency. The synthesis shows consistent patterns across the Java Sea and surrounding waters, confirming the ecological sensitivity of small pelagic fish to oceanographic variability. The study concludes that SST anomalies are a key driver of fisheries productivity changes in northern East Java waters.